Access to justice for conservation of the biodiversity: an important component of environmental justice - Ansari, Abdul Haseeb; Al-Gasim, Saa Abu (AENSI Publications, Jordan, 2014)
For conservation of the biodiversity and for maintaining anessential balance between all flora and fauna and the achieving the ultimate goal of sustainable development, access to justice is a must. Only because of easy and fast institution and disposal of environmental pollution and degradation cases, these objectives can be achieved and poor and marginal people can get justice. It is also notable that the right to access to justices is crucial for right to information and right to participate in environmental decision-makings. The solution lies in relaxing the requirement of locus standi to pave the way for public interest/social interest litigation, which the Indian Apex Courts have evolved and are practicing. Nevertheless, it has to be so only in genuine cases. The authors suggest that the Indian practice should be internalised by other states, but with necessary safeguards. The Australian practice of Law Clearing Houses and the Canadian practice of providing mitigation or exemption on cost are also good practices for others to emulate. The authors feel that in order to provide funding for public interest cases, every state should create a fund and extend legal and procedural support through legal aid clinics.